2013
DOI: 10.1088/0264-9381/31/2/025024
|View full text |Cite
|
Sign up to set email alerts
|

‘Vacuum-like’ Hadamard states for quantum fields on curved spacetimes

Abstract: Abstract. We present a modification of the recently proposed Sorkin-Johnston states for scalar free quantum fields on a class of globally hyperbolic spacetimes possessing compact Cauchy hypersurfaces. The modification relies on a smooth cutoff of the commutator function and leads always to Hadamard states, in contrast to the original Sorkin-Johnston states. The modified Sorkin-Johnston states are, however, due to the smoothing no longer uniquely associated to the spacetime.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(71 citation statements)
references
References 39 publications
0
71
0
Order By: Relevance
“…Yet, the ensuing state fails to obey to the Hadamard property as first observed in [13]. This seems to be a generic feature which can be cured only by introducing suitable ad-hoc cut-off functions as proposed in [6]. This is in sharp contrast with the behaviour of the FP state in space-times of infinite lifetime.…”
Section: Introductionmentioning
confidence: 95%
“…Yet, the ensuing state fails to obey to the Hadamard property as first observed in [13]. This seems to be a generic feature which can be cured only by introducing suitable ad-hoc cut-off functions as proposed in [6]. This is in sharp contrast with the behaviour of the FP state in space-times of infinite lifetime.…”
Section: Introductionmentioning
confidence: 95%
“…Subsequently Sorkin (2011a) showed that the construction is also valid in the continuum, and can be used to give an alternative definition of the quantum field theory vacuum. This Sorkin-Johnston (SJ) vacuum provides a new insight into quantum field theory and has stimulated the interest of the algebraic field theory community (Fewster and Verch 2012;Brum and Fredenhagen 2014;Fewster 2018). The SJ vacuum has also been used to calculate Sorkin's spacetime entanglement entropy (SSEE) (Bombelli et al 1986;Sorkin 2014) in a causal set Sorkin and Yazdi 2018).…”
Section: Overviewmentioning
confidence: 99%
“…Since the SJ vacuum is intrinsically defined, at least in finite spacetime regions, one has a uniquely defined vacuum. As a result, the SJ state has generated some interest in the broader algebraic field theory community (Fewster and Verch 2012;Brum and Fredenhagen 2014;Fewster 2018). For example, while not in itself Hadamard in general, the SJ vacuum can be used to generate a new class of Hadamard states (Brum and Fredenhagen 2014).…”
Section: The Sorkin-johnston (Sj) Vacuummentioning
confidence: 99%
“…However, even if the PJ operator is itself 8 The use of the L 2 inner product for the SJ modes suggests the possibility that the SJ vacuum exists in a different sector of the theory. 9 Allen's theorem continues to hold in a finite region of spacetime as long as we choose this region to be symmetric about τ = 0, where τ is the time in hyperbolic coordinates (69). 10 In the causal set case we cannot take these temporal cutoffs to infinity, but we try to reach an asymptotic regime.…”
Section: The Massless De Sitter Sj Vacuummentioning
confidence: 99%